A importância do problem-posing na educação para sustentabilidade nos cursos de administração - Santos, Carlos Jonathan da Silva (2021)
This thesis fits into studies focused on education for sustainability in Business Administration courses and argues that promoting teaching-learning experiences oriented towards problem-posing creates opportunities for teaching sustainability in Business Schools to be potentially more transformative. To support this argument, the objective was to discuss and evaluate the reflections of students submitted to the analysis of a case study using a problem-posing (PP) and another problem-solving (PS) protocol, in order to analyze possible benefits of each other from the point of view of transformative learning (TL). To this end, protocols of teaching cases were developed and applied from the perspective of PP and PS comparing them in relation to the types of reflection achieved by students in a Business Administration course who attended the discipline of Strategic Management for Sustainability (SMS). Among the countless ways in which business-oriented education can be instigated in business schools, it was felt that looking at the way we teach students to problematize socioenvironmental demands and dilemmas in the classroom contributes to the advancement of pedagogical experiences that seek to foster paradigmatic and epistemological changes. Thus, by putting the PP debate in the Administration field as another way of promoting this deeper change, it is intended to cover a gap in the literature, especially under the approach of transformative learning from a social and critical perspective. The study was composed of the analysis of written texts and recorded audios of 173 students from three classes who took the SMS course. The 173 students were divided into groups of approximately four students, which totaled 44 groups, covering the three classes. All groups used the same teaching case; however, 21 groups were guided by a PP protocol, and 23 groups were guided by a PS protocol. After the students produced the texts and recorded the audios of the discussions that emerged from the respective protocols, their reflections were categorized and discussed in successive rounds of analysis and validation. The analysis categories defined a priori followed Jack Mezirow's dimensions of reflection: reflection of content, process and premise. Also, the groups that presented reflection of the premise, again had their materials analyzed, by a posteriori categorization, designed to understand whether the reflection of the premise was focused on an axis of rational processes and means, of metaphors and assumptions, or even an emancipatory axis, according to the theoretical framework of analysis constructed for this purpose. The results showed that the content and process reflections appeared similarly in the two protocols. However, the biggest difference appears when it is observed for the premise reflection, since, in comparison with the PS protocol, almost a quarter more of the PP protocol groups were involved in some form of premise reflection, indicating that the protocol of PP made a difference. The study presents theoretical and practical-methodological contributions, when discussing the meaning of PP in the teaching of Administration oriented to sustainability in the light of TL theories, and in making implications for students, teachers, business schools, as well as for the construction of protocols and teaching materials that promote PP.